KNOWLEDGE TRANSFER IN ROMANIAN UNIVERSITY QUADRUPLE HELIX ECOSYSTEMS (Nonconventional Technologies Review, 2021)
Lately, there has been an unprecedented increasing attention paid to the dimension of knowledge transfer from HEIs to the bigger ecosystems and also to the collaboration existing between stakeholders within the innovation ecosystems, particularly due to the growing demands for innovations and their commercialization. Additionally, the paradigm shift from triple helix to the quadruple helix has prompted the necessity for more research on the collaboration between actors, the drivers of success and also the challenges encountered. This research aims to analyse the perceptions of the stakeholders through a qualitative study, focusing mainly on solutions to increase the effectiveness of knowledge transfer. The results acknowledged the necessity for effective collaborations for the knowledge transfer, possible only through the engagement of all stakeholders. The study contributes to the existing literature by revealing the challenges which emerge from the collaboration of the actors involved in the knowledge transfer.
Keywords: knowledge transfer; triple helix; quadruple helix; stakeholders; HEIs